ANALISIS PERKEMBANGAN USAHA SIMPAN PINJAM KOPERASI PEGAWAI - Marcella, Cesillia; Asriati, Nuraini; Khosmas, F.Y. (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstractThis thesis is entitled "Analysis of the Development of Savings and Loans BusinessCooperatives for Civil Servants, Tanjungpura University. The method used isdescriptive method. The form of the research is qualitative description. Datacollection techniques in this study are: direct communication with data collectiontools, interview guides, direct observation with data collection tools, observationsheets, documentary studies with data collection tools, Cooperative data archives.With the results of the study as follows: 1) That the development of the savings andloan business of the Public Servant Cooperative of the University of TanjungpuraPontianak for the period 2017-2019, has seen an increase in the growth of theremaining operating results from year to year where in 2017 it increased by 19%and then experienced an increase of 19%. increase in 2019 by 30%,. 2) Whereas theefforts made by the management in developing the existing businesses at the PublicServant Cooperative of Tanjungpura University Pontianak, while the efforts madeare by developing capital, managerial skills, improving the performance of themanagement and participation of members. 3) Whereas there are 2 factors thatinfluence the development of the efforts of the Public Servant Cooperative atTanjungpura University, Pontianak, namely internal factors in the form of factors,namely capital development, managerial skills, management performance andmember participation, while external factors are caused by the motivation of thecooperative community, supervision from the cooperative supervisory body. andcaused by the system of infrastructure, services, education and counseling.Keyword : Analysis of Savings and Loan Business Development, TanjungpuraUniversity Civil Servant Cooperative.